Reversible Uptake of CO2 by Pincer Ligand Supported Dimetallynes. (26th February 2022) - Caise, Alexa; Griffin, Liam P.; McManus, Caitilín; Heilmann, Andreas; Aldridge, Simon
Abstract: We report on the reversible uptake of carbon dioxide by dimetallynes featuring ancillary hemi‐labile pincer ligands. Insertion into the Ge−Ge/Sn−Sn bonds yields species containing an E(CO2 )E unit, with the mode of ligation of the CO2 fragment determined crystallographically being found to be dependent on the identity of the Group 14 element. The thermodynamics of CO2 uptake/loss can be established through VT NMR (Δ H °=+24.6(2.3) kJ mol −1, Δ S °=+64.9(3.8) J mol −1 K −1, Δ G °298 =+5.3(1.9) kJ mol −1 for the loss of CO2 in the Ge case), and the chemical consequences of reversibility demonstrated by thermodynamically‐controlled exchange reactions. Abstract : The reversible uptake of CO2 by dimetallynes featuring ancillary hemi‐labile pincer ligands is reported. Insertion into the Ge−Ge/Sn−Sn bonds yields species containing an E(CO2 )E unit, with the mode of ligation of the CO2 fragment being dependent on the Group 14 element. The thermodynamics of CO2 uptake can be established through VT NMR, and the chemical consequences of reversibility demonstrated by thermodynamically‐controlled exchange reactions.